Utilizing Diagnostic Musculoskeletal Ultrasound for Assessment of the Infraspinatus Muscle and Tendon: Implications for Rehabilitation Professionals - Robert C Manske; Michael Voight; Chris Wolfe; Phil Page (International Journal of Sports Physical Therapy)
The rotator cuff, comprising the subscapularis, supraspinatus, infraspinatus, and teres minor muscles, plays a crucial role in stabilizing the glenohumeral joint by securing the head of the humerus within the glenoid cavity of the scapula. The tendinous insertions of these muscles generate tension within the capsule, enhancing joint stability during muscular activity. The rotator cuff is susceptible to damage from disease, injury, or trauma, which can result in tears or ruptures of one or more tendons. The evaluation of the infraspinatus muscle and tendon is vital for diagnosing and managing various shoulder pathologies. Accurate imaging to determine the specific muscle involvement and injury severity significantly impacts treatment decisions. Diagnostic musculoskeletal ultrasound (MSK-US) has emerged as a valuable tool for assessing the infraspinatus muscle and tendon, offering real-time, dynamic assessment capabilities essential for precise diagnosis and effective rehabilitation planning. This article reviews the utility and advantages of MSK-US in evaluating the infraspinatus muscle and tendon, emphasizing technique specifics, diagnostic accuracy, and comparative efficacy against other imaging modalities. It details a systematic approach to the ultrasound examination technique for the infraspinatus, including patient positioning and identification of common pathologies such as tears, tendinopathy, and calcifications. With recent advancements in transducer strength, image resolution, and operator training, ultrasound serves as an excellent alternative imaging modality for diagnosing rotator cuff tears. This article aims to equip rehabilitation professionals with a comprehensive understanding of MSK-US as a diagnostic tool for the infraspinatus, promoting more precise diagnosis, treatment planning and improved patient outcomes.